Split‐Cre recombinase effectively monitors protein–protein interactions in living bacteria. Issue 3 (29th January 2014) - O'Brien, Sean P.; DeLisa, Matthew P.
Abstract The ability of Cre recombinase to excise genetic material has been used extensively for genome engineering in prokaryotic and eukaryotic cells. Recently, split‐Cre fragments have been described that advance control of recombinase activity in mammalian cells. However, whether these fragments can be utilized for monitoring protein‐protein interactions has not been reported. In this work, we developed a protein‐fragment complementation assay (PCA) based on split‐Cre for monitoring and engineering pairwise protein interactions in living Escherichia coli cells. This required creation of a dual‐fluorescent reporter plasmid that permits visualization of reconstituted Cre recombinase activity by switching from red to green in the presence of an interacting protein pair. The resulting split‐Cre PCA faithfully links cell fluorescence with differences in binding affinity, thereby allowing the facile isolation of high‐affinity binders based on phenotype. Given the resolution of its activity and sensitivity to interactions, our system may prove a viable option for poorly expressed or weakly interacting protein pairs that evade detection in other PCA formats. Based on these findings, we anticipate that our split‐Cre PCA will become a highly complementary and useful new addition to the protein‐protein interaction toolbox.